Low-Cost Solution for Assessment of Urban Flash Flood Impacts Using Sentinel-2 Satellite Images and Fuzzy Analytic Hierarchy Process: A Case Study of Ras Ghareb City, Egypt - Mohammed Sadek; Xuxiang Li (Advances in Civil Engineering)
Natural hazards are indeed counted as the most critical challenges facing our world, represented in floods, earthquakes, volcanoes, hurricanes, and forest fires. Among these natural hazards, the flash flood is regarded the most frequent. In this work, we utilized two Sentinel-2 satellite images, before and after the flash flood, SRTM and photos captured by using a helicopter. This paper aims at three prime objectives. Firstly, the flood influence is determined on the city of Ras Ghareb, Egypt, based on analyzing free satellite data (Sentinel-2 images). Secondly, fuzzy the analytical hierarchy process (FAHP) method and a geographical information system (GIS) are integrated for flood risk analysis and evaluation in the flood-prone area. Finally, such a flood vulnerability map is used as an index to assist the decision-makers prepare for probable flooding. FAHP is preferable as it can cater to the uncertainties in data and analysis. As a result, FAHP is appropriate to determine the flood-vulnerable area in cities especially due to the matching with the most destroyed areas identified by the change detection between the two Sentinel-2 images. Then, the decision-maker can depend on Sentinel-2 images to estimate the flood influence through a regional scale or applying the FAHP on cities susceptible to flash floods in case of unavailable satellite images to contribute in establishing an early warning system enough to the evacuation of the risky areas.